(untitled) (Research, Society and Development, 2022)
The Special Educational Service (SES) is the object of study of many researchers, whose purpose is to investigate how interventions occur with the target audience of Special Education students. This study aimed to know the professionals profiles that is responsible for SES in the Multifunctional Resource Room (MRR) of schools in two poles of the Municipal Education Network in Niterói, a municipality in the state of Rio de Janeiro. Analysis and data collection was carried out using the quantitative-qualitative mixed method. Data collection to outline the professional’s profile was carried out through a questionnaire and semi-structured interview. The results of the interviews allowed a concrete view of the current scenario of MRR teachers of the schools surveyed, as well as the knowledge of the practices, interventions, resources and materials of Assistive Technology applied to Specialized Educational Service (SES), considered as essential for the teaching-learning process in inclusive education.